WORLD REGIONAL STUDIES AS A RESEARCH FRAMEWORK AND ACADEMIC DISCIPLINE - E. V. Koldunova (Vestnik MGIMO-Universiteta)
Dynamic development of international processes at the regional level, various trajectories of regionalization in Europe, Asia, Latin America and other parts of the world created a complex and multidimensional picture of the contemporary international relations. However Social Sciences and IR retained a distinct eurocentrism. This eurocentrism only partly meant that students of IR did not take into account non-European or non-Western realities. Thus, a German Scholar J. Vullers from German Institute of Global and Area Studies analyzing in 2014 three leading International Relations journals (International Organization, World Politics, European Journal of International Relations) diagnosed a serious geographic imbalance in the international studies, which meant a very limited number of articles based on the nonWestern empirical data.Even with such geographic imbalance in IR studies more important for preserving eurocentrism there was the absence of non-Western IR theories or IR theories originating from non-Western political context. The collective monograph edited by Barry Buzan and Amitav Acharya focused exactly on this problem. The title of the book was provocatively asking why there is no non-Western IR theory. Thus, the book in question provoked a lively academic debate on the topic. Russia was not covered in this book. Therefore, this very fact gives one some reasons to reflect on how Russian research in the field may face a double challenge of a changing international environment and an inappropriate level of its intellectual assessment. Against this background this article analyzes World Regional Studies, a research framework and discipline, which is rapidly developing in Russia and may to some extent contribute to a more correct understanding of the international processes.